Analisis Pengaruh Komunikasi dan Motivasi terhadap Kinerja pada PT. Rentokil Initial Indonesia - Rauddina Alyani (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Communication is the interest of everyone to socialize with others. A person will find it difficult to connect with others without communication. Motivation gives an employee a goal in doing his job. Work motivation is a drive that arises both from within and from outside that causes a person to carry out a series of activities to achieve a personal goal and company goal. Therefore, communication and motivation greatly affect employee performance. The discussion in this study aims to analyze how much influence communication and motivation have on the performance of employees of PT Rentokil Initial Indonesia. This study uses a quantitative approach, using simple linear regression analysis to evaluate the relationship between communication, motivation, and employee performance. The number of samples in this study were 103 employees as respondents. Data collection techniques were conducted by interview, observation, and questionnaire. Data processing was carried out using SPSS version 25. Then the results obtained show that effective communication and motivation significantly impact overall employee performance.